Construction of the Agrotourism Dimensional Model: Perspective of Attraction of Visitor Experiences in Agrotourism Salak, Sibetan Karangasem Bali - I Dewa Ayu Tita Permata Tabita; Ida Ayu Suryaningsih (Bioculture Journal, 2023)
Tourism has become one of the industries that has a major impact on Bali's economic growth. This study aims to explore the various factors that build important dimensions as a determinant of the formation of visitor experience in agro-tourism. The collecting data  by interviews related to the form of expectations and responses of visitors as informants about the Sibetan agro-tourism object. This type of data is for exploring the dimensions and factors that reflect the dimensions to construct a measurement scale. The next step is to classify by group category to build dimensions, then the data  processed using descriptive statistical analysis tools, namely confirmatory factor analysis.   The indicator that produces the largest loading factor is determined as the indicator that most strongly reflects the variable in question. This result shows that the better the Tourist Visit Experience to Sibetan Agrotourism object, Karangasem, the more loyal these visitors are to Sibetan Agrotourism object, Karangasem. Based on the results of the study, information was obtained that based on the Experience of Tourists visiting Sibetan Agrotourism objects, Karangasem the biggest factor influencing tourists to visit Sibetan Agrotourism objects, Karangasem is the Security factor, then followed by the Coolness of tourist objects, Service and Hospitality, Order and Uniqueness and Beauty of Sibetan Agrotourism objects, Karangasem. Tourist Visiting Experience to Sibetan Agrotourism Object, Karangasem has a positive and significant effect on Visitor Loyalty.